(NnEAPOLITANSKIE PESNIs (NNOTA(B. s - (N|(B.(NdI kAPUAs ((NsANKT(B-(NpETERBURGs (NlANXs (NpLANETA MUZYKIs, 2024)
(NiTALXQNSKIJ KOMPOZITOR |DUARDO dI kAPUA QWLQETSQ ODNIM IZ SAMYH IZWESTNYH AWTOROW NEOPOLITANSKIH PESEN Ts
Keywords: (NrOMANSs